Vacuum thermal switch made of phase transition materials considering thin film and substrate effects. (June 2015) - Yang, Yue; Basu, Soumyadipta; Wang, Liping
Abstract: In the present study, we theoretically demonstrate a vacuum thermal switch based on near-field thermal radiation between phase transition materials, i.e., vanadium dioxide (VO2 ), whose phase changes from insulator to metal at 341 K. Strong coupling of surface phonon polaritons between two insulating VO2 plates significantly enhances the near-field heat flux, which on the other hand is greatly reduced when the VO2 emitter becomes metallic, resulting in strong thermal switching effect. Fluctuational electrodynamics incorporated with anisotropic wave propagation predicts more than 80% heat transfer reduction at sub-30-nm vacuum gaps and 50% at vacuum gap of 1 μm. Furthermore, the penetration depth inside the uniaxial VO2 insulator is studied at the vacuum gap of 50 nm, suggesting the possible impact of reduced VO2 thickness on the near-field thermal radiation with thin-film structures. By replacing the bulk VO2 receiver with a thin film of several tens of nanometers, the switching effect is further improved over a broad range of vacuum gaps from 10 nm to 1 μm. Finally, the effect of SiO2 substrate for the thin-film emitter or receiver is also considered to provide insights for future experimental demonstrations. By controlling heat flow with near-field radiative transport, the proposed vacuum thermal switch would find practical applications for energy dissipation in microelectronic devices and for the realization of thermal circuits. Highlights: Near-field thermal switching was theoretically demonstrated with phase change VO2 . Radiative heat flux was reduced by 80% at sub-30-nm vacuum gaps or 50% at 1 μm. Strong phonon coupling between insulating VO2 emitter and receiver was elucidated. Thin-film structures were studied for achieving stronger thermal switching effect. Effect of SiO2 substrate was investigated for thin-film vacuum thermal switches.